2003
DOI: 10.2134/jeq2003.2240
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants in the Environment

Abstract: The half-lives of some persistent organic pollutants (POPs) in environmental compartments such as soil and air can be as long as decades. In spite of the hydrophobicity of many POPs, the literature contains reports of their uptake by, and translocation through, a variety of plants. Both these observations prompt the investigation of whether a vegetation-based environmental compartment such as compost contains significant residues of POPs. Previous reports imply that residues of technical chlordane will be foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The biomass values and intraplant contaminant distribution reported here are similar to our previous findings for the uptake and translocation of weathered chlordane and p,p′-DDE by C. pepo (34,44). In addition, the percent of contaminant phytoextracted also fits within the range previously reported.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The biomass values and intraplant contaminant distribution reported here are similar to our previous findings for the uptake and translocation of weathered chlordane and p,p′-DDE by C. pepo (34,44). In addition, the percent of contaminant phytoextracted also fits within the range previously reported.…”
Section: Resultssupporting
confidence: 90%
“…Table 2 shows that several indices of contaminant uptake and translocation are significantly greater for ssp pepo than for ssp texana. Our previous studies focused on a narrow range of cultivars within ssp pepo and have consistently reported significant phytoextraction of weathered chlordane (44,49) and p,p′-DDE (33,34). As described above, White (34) did show different uptake potentials of p,p′-DDE for a small number of cultivars of ssp texana and pepo.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, significant shifts in the compositional profile and chiral profile were observed in the plant tissues. In another study by the same group, chiral GC/ion trap-MS was used to examine technical chlordane residues in a variety of compost products (13 commercial and 39 municipal) (119). Compositional and enantiomeric profiles were obtained.…”
Section: Chiral Contaminantsmentioning
confidence: 99%